PENGEMBANGAN MODEL PBL DALAM UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Ali Wardana; Anwar Ardani (Universitas Muhammadiyah Lampung, 2022)
The purpose of this study was to test learning tools with valid PBL models, learning with practical PBL models, and developing tools with PBL mood models to improve students' critical thinking skills with PBL models. This research is an R&D research. The instrument used is a test to measure critical thinking skills. The learning device is valid based on the average expert validation score in the good category, practical from the practicality score of student responses, and effective as seen by the increase in the paired sample t test. The results of this study are learning tools with a valid PBL model, learning with practical PBL models, and the development of tools with PBL mood models improve students' critical thinking skills with the PBL model.